Implants of 6 mm vs. 11 mm lengths in the posterior maxilla and mandible: a 1-year multicenter randomized controlled trial - Guljé, Felix; Abrahamsson, Ingemar; Chen, Stephen; Stanford, Clark; Zadeh, Homayoun; Palmer, Richard (Clinical oral implants research, 2013)
Background and aim In cases with limited bone height, short implants could be a good alternative to augmentation procedures. The aim of this randomized controlled trial was to compare the clinical performance of implants of 6 mm or 11 mm in length in the posterior region. Materials and methods In this multicenter trial (six study sites), 95 subjects were included. Subjects were randomly allocated to receiving implants with lengths of either 6 or 11 mm both with a diameter of 4 mm (OsseoSpeed™ 4.0 S; Astra Tech AB; Mölndal, Sweden). In all cases, there had to be sufficient bone height to allow placement of an implant of at least 11 mm in length. Two or three implants were placed per subject using one‐stage surgery with a 42–48 days' healing period before loading. They were restored with a screw‐retained splinted fixed prosthesis. Clinical and radiographic examinations were performed preoperatively, postsurgery, at loading, and 6 and 12 months after prosthesis placement. Results A total of 208 implants were inserted in 49 subjects receiving 6‐mm implants (test) and in 46 subjects receiving 11 mm implants (control). Two 6‐mm implants failed before loading and one 6 and 11 mm implants failed before 1‐year evaluation. From loading to the 12 months' follow‐up, a mean marginal bone gain of 0.06 mm in the 6 mm group and 0.02 mm in the 11 mm group was found (P = 0.478). Soft tissue behavior was equal in both groups (Bleeding and plaque [P = 1.0] probing depth [P = 0.91]). Conclusion One‐year data indicate that treatment with the 6 mm implants is as reliable as treatment with the 11 mm implants. This provides a good treatment option in situations with limited bone height in the premolar and molar regions. Whether or not short implants provide a predictable treatment alternative to bone augmentation procedures remains to be investigated in the future randomized controlled clinical trials.